Indole scaffolds as a promising class of the aryl hydrocarbon receptor ligands - Dvořák, Zdeněk; Poulíková, Karolína; Mani, Sridhar (European journal of medicinal chemistry, 2021)
The aryl hydrocarbon receptor (AhR), deemed initially as a xenobiotic sensor, plays multiple physiological roles and is involved in various pathophysiological processes and many diseases' etiology. Therefore, the therapeutic and chemopreventive targeting of AhR is a fundamental issue. To date, thousands of structurally diverse ligands of AhR have been identified. The bottleneck in targeting the AhR is that it is a Janus-faced player with beneficial vs. harmful effects in the ligand-specific context. A distinct structural class of the AhR ligands is those with indole-based scaffolds. The present review summarizes the knowledge on the existing indole-derived AhR ligands, comprising natural and dietary compounds, synthetic compounds including clinically used drugs, endogenous intermediary metabolites, and catabolites produced by human microbiota. The examples of novel, indole ring containing, rational design based AhR ligands are presented. The molecular, in vitro, and in vivo effects are described.
Keywords: Receptors, Aryl Hydrocarbon; Aryl hydrocarbon receptor; Ligands; receptory aromatických uhlovodíků; Rational design; Animals; lidé; ligandy; Humans; Indoles; zvířata; indoly